1902
DOI: 10.1002/zaac.19020320142
|View full text |Cite
|
Sign up to set email alerts
|

Beiträge zur Kenntnis anorganischer Kolloïde

Abstract: Beeuglich der Iitteratur uber die Kolloi'de sei auf LOTTERMOSER: An-1. c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1903
1903
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The author pronounces innumerable thanks to colleagues who have invaluably supported the author in the area of nanocomposites during the last 17…”
Section: Acknowledgementsmentioning
confidence: 97%
See 1 more Smart Citation
“…The author pronounces innumerable thanks to colleagues who have invaluably supported the author in the area of nanocomposites during the last 17…”
Section: Acknowledgementsmentioning
confidence: 97%
“…In this context it is worth noting that fundamental studies on nanoparticles themselves were performed with metals already 100 years ago. While dialysis experiments showed that silver 17 or gold 18 species which appeared to be dissolved in water existed as particles and not as individual atoms or assemblies of only a few atoms, the particle dimensions in a nanocomposite of gold embedded in a glass matrix were measured with ultramicroscopes as early as in 1903 (these instruments allowed the visualisation of nanoparticles with the help of light scattering). 19 Values down to y6 nm, which was in the range of the resolution limit of the instrument, were found.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…The main strategy for nanoparticle synthesis is based on the chemical reduction in liquids. Possible reducing agents are phosphor [11,12], formaldehyde [13], acetone [14], citrate [10,15,16], ascorbic acid [17], tannic acid [18][19][20], salicylic acid [20], oxalic acid [15], ethyl alcohol [21], hydroxylamine [22,23] or sodium borohydride. Here we can distinguish between a direct reduction with a reducing agent and the reduction in presence of organic ligands.…”
Section: Synthesis Of Metal Nanoparticles 21 General Strategiesmentioning
confidence: 99%
“…The latter particles represent the so-called monolayer protected clusters or particles, also Brustparticles [7][8][9][10]. Possible reducing agents are phosphor [11,12], formaldehyde [13], acetone [14], citrate [10,15,16], ascorbic acid [17], tannic acid [18][19][20], salicylic acid [20], oxalic acid [15], ethyl alcohol [21], hydroxylamine [22,23] or sodium borohydride. In general, the strength and the amount of the used reducing agent have a key effect to the resulting particle size.…”
Section: Synthesis Of Metal Nanoparticles 21 General Strategiesmentioning
confidence: 99%